Preventive Effects of Probiotic Supplementation on Neonatal Hyperbilirubinemia Caused by Isoimmunization - Mutlu, Mehmet; Aslan, Yakup; Kader, Şebnem; Aktürk Acar, Filiz (American Journal of Perinatology, 2019)
Objective Probiotic supplementation can help to improve recovery from jaundice by reducing enterohepatic circulation through the regulation of intestinal microbial flora. The aim of our study was to investigate the effect of probiotic supplementation on neonatal hyperbilirubinemia caused by isoimmunization alone.Study Design Sixty neonates were randomly divided into a placebo group and a probiotic group (Lactobacillus rhamnosus GG). Serum total bilirubin (STB) levels were measured at birth and at 4, 8, 16, 24, and 36 hours of treatment (and at 48, 60, and 72 hours if necessary). Duration of phototherapy, rephototherapy requirements, and daily meconium evacuation were recorded.Results STB and rebound STB levels at 36 hours were lower in the probiotic group than in the placebo group (p = 0.01 and p = 0.006, respectively). Meconium evacuation was more frequent in the probiotic group than in the placebo group on the second and third days of life (p = 0.002 and 0.009, respectively).Conclusion Probiotics do not affect STB levels in the first 24 hours of life or duration of phototherapy in neonates with jaundice caused by blood group incompatibility. The effect of probiotic supplementation by reducing enterohepatic circulation occurs at 36 hours of life in newborns with isoimmunization.
Keywords: jaundice; probiotic; isoimmunization; meconium